Antimicrobial activity of the essential oil from Lippia sidoides, carvacrol and thymol against oral pathogens - Botelho,M.A. (2007)
Dental caries and periodontal disease are associated with oral pathogens. Several plant derivatives have been evaluated with respect to their antimicrobial effects against such pathogenic microorganisms. Lippia sidoides Cham (Verbenaceae), popularly known as "Alecrim-pimenta" is a typical shrub commonly found in the Northeast of Brazil. Many plant species belonging to the genus Lippia yield very fragrant essential oils of potential economic value which are used by the industry for the commercial production of perfumes, creams, lotions, and deodorants. Since the leaves of L. sidoides are also extensively used in popular medicine for the treatment of skin wounds and cuts, the objective of the present study was to evaluate the composition and antimicrobial activity of L. sidoides essential oil. The essential oil was obtained by hydro-distillation and analyzed by GC-MS. Twelve compounds were characterized, having as major constituents thymol (56.7%) and carvacrol (16.7%). The antimicrobial activity of the oil and the major components was tested against cariogenic bacterial species of the genus Streptococcus as well as Candida albicans using the broth dilution and disk diffusion assays. The essential oil and its major components thymol and carvacrol exhibited potent antimicrobial activity against the organisms tested with minimum inhibitory concentrations ranging from 0.625 to 10.0 mg/mL. The most sensitive microorganisms were C. albicans and Streptococcus mutans. The essential oil of L. sidoides and its major components exert promising antimicrobial effects against oral pathogens and suggest its likely usefulness to combat oral microbial growth.